Pengembangan E-LKPD Interaktif Didukung Kasus Kemaritiman Berbantuan Google Sites Pada Materi Termokimia - Fitiriani, Rita; Yulita, Inelda; Adisaputra, Adisaputra (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Maritim Raja Ali Haji, 2025)
In the learning process, chemistry teachers still rely on printed teaching materials that focus on conceptual content delivery without integrating students daily life contexts. Specifically, chemistry instruction has not been linked to the local characteristics of the Riau Archipelago region, which holds significant maritime potential. Therefore, an interactive E-LKPD supported by maritime case studies and facilitated through Google Sites was developed for thermochemistry material. This research aims to produce interactive E-LKPD teaching materials supported by maritime cases using Google Sites in the topic of thermochemistry. This research is a type of Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The developed teaching material was validity by one subject material validators and one media validators. The research subjects are two chemistry teachers and 27 students from class XI.3 of SMA Negeri 5 Tanjungpinang. The results showed that the development of the interactive E-LKPD supported by maritime case studies using Google Sites for thermochemistry material receive a validity score of 93,21% from the material validator and 92,5% from the media validator, both categorized as very valid. The practically scores from teachers and students were 95,24% and 96,24%, respectively category as very practical. These results indicate that developed teaching material is highly feasible for use in learning.